2021
DOI: 10.3390/cells10071836
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Virus Infection on Microglia and Accelerated Brain Aging

Abstract: Microglia are the resident immune cells of the central nervous system contributing substantially to health and disease. There is increasing evidence that inflammatory microglia may induce or accelerate brain aging, by interfering with physiological repair and remodeling processes. Many viral infections affect the brain and interfere with microglia functions, including human immune deficiency virus, flaviviruses, SARS-CoV-2, influenza, and human herpes viruses. Especially chronic viral infections causing low-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 246 publications
(314 reference statements)
0
21
0
Order By: Relevance
“…As cell-cell fusion is a major trigger of cellular senescence, viruses may have developed the ability to exploit host fusogens, promoting premature aging ( Gal et al., 2019 ). Indeed, epidemiological and research data have associated neurotropic viruses with accelerated brain aging and neurodegenerative disorders ( Mavrikaki et al., 2021 ; Sait et al., 2021 ; Filgueira et al., 2021 ; Dowd and McKernan, 2021 ). Along these lines, herpes simplex virus 1 (HSV-1) and human herpesvirus 6 (HHV-6) have been associated with Alzheimer’s disease (AD) and multiple sclerosis (MS) respectively, while human immunodeficiency virus type 1 (HIV-1) contributes to HIV-associated neurocognitive disorders (HAND, 18-19).…”
Section: Introductionmentioning
confidence: 99%
“…As cell-cell fusion is a major trigger of cellular senescence, viruses may have developed the ability to exploit host fusogens, promoting premature aging ( Gal et al., 2019 ). Indeed, epidemiological and research data have associated neurotropic viruses with accelerated brain aging and neurodegenerative disorders ( Mavrikaki et al., 2021 ; Sait et al., 2021 ; Filgueira et al., 2021 ; Dowd and McKernan, 2021 ). Along these lines, herpes simplex virus 1 (HSV-1) and human herpesvirus 6 (HHV-6) have been associated with Alzheimer’s disease (AD) and multiple sclerosis (MS) respectively, while human immunodeficiency virus type 1 (HIV-1) contributes to HIV-associated neurocognitive disorders (HAND, 18-19).…”
Section: Introductionmentioning
confidence: 99%
“…Altered microbiota composition has also been associated with the development of NDs, therefore microbiome-microglia interactions might influence NDs pathogenesis ( 68 ). Viruses which are also associated with the development of NDs and can also interfere with microglia functions ( 91 ). Therefore, since alternation in microbiota can influence microglia immune responses against viral infection, microbiota-virus-microglia interactions could also influence the pathogenesis of NDs.…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment studies observed an increased population of myeloid cells (in the pancreas, intestine, kidney, lung, liver) and microglia (in the brain), which form part of the innate immune response against the virus. These cell types have a known role in phagocytosis and anti-inflammation, biochemical pathways commonly observed in response to viral infection [119, 120]. Antigen-presenting cells (A.P.C.)…”
Section: Discussionmentioning
confidence: 99%